2006
DOI: 10.1002/ajh.20685
|View full text |Cite
|
Sign up to set email alerts
|

Circumstances of death in adult sickle cell disease patients

Abstract: The purpose of the study was to analyze clinical and/or autopsy findings at the time of death among adults with sickle cell disease (SCD) at Howard University in Washington, DC over a 25-year period. A single physician recorded circumstances of death among 141 adult SCD patients he treated and knew well from 1976 to 2001. These findings were determined by autopsy report and/or clinical assessment. In a subset of 31 patients, autopsy records were reviewed for reports of iron deposition in liver and heart and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
186
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(204 citation statements)
references
References 20 publications
(24 reference statements)
7
186
1
2
Order By: Relevance
“…Loss of HRV is also a significant risk factor for cardiovascular adverse events, including sudden death, in the general population (45). Interestingly, up to 23% of deaths in adults with SCD are so-called "sudden death" events with no detectable cause found at autopsy (4,46,47). The present study demonstrates significant withdrawal of parasympathetic activity in response to transient hypoxia in subjects with SCD that was not present in non-SCD control subjects.…”
Section: Discussionmentioning
confidence: 48%
“…Loss of HRV is also a significant risk factor for cardiovascular adverse events, including sudden death, in the general population (45). Interestingly, up to 23% of deaths in adults with SCD are so-called "sudden death" events with no detectable cause found at autopsy (4,46,47). The present study demonstrates significant withdrawal of parasympathetic activity in response to transient hypoxia in subjects with SCD that was not present in non-SCD control subjects.…”
Section: Discussionmentioning
confidence: 48%
“…In adults with Hb SS and Sb(0) followed at a tertiary care medical care center, the median age of death was 58 years of age [22], still significantly lower than that contemporary life-expectancy for African-American adults without SCD. Cardiopulmonary disease remains the major, but not exclusive, cause of death in adults with SCD [23][24][25][26]. More specifically, a significant proportion die from causes related to chronic organ dysfunction including pulmonary hypertension, renal failure, thromboembolism, infections and excessive iron stores.…”
Section: Mortality In Scdmentioning
confidence: 99%
“…More specifically, a significant proportion die from causes related to chronic organ dysfunction including pulmonary hypertension, renal failure, thromboembolism, infections and excessive iron stores. [24]. Treatments targeting vascular dysfunction to prevent major organ damage are under evaluation and may have the greatest impact in adults with SCD [27].…”
Section: Mortality In Scdmentioning
confidence: 99%
“…The median age at death is 42 years for men and 48 years for women [2]. Pulmonary complications, acute chest syndrome (ACS) and PAH account for a large proportion of deaths in adults with SCD [3,4]. One retrospective study reported a median survival of 25.6 months for SCD patients with PAH confirmed by right heart catheterization [5].…”
Section: Introductionmentioning
confidence: 99%